Edukasi Peran Istri yang Bekerja Dalam Membantu Ekonomi Keluarga Pada Ibu-Ibu Majelis Taklim Dusun V Kampung Baru Kualu - khairunisa, Madona; Lubis, Haniah; Nurlaili, Nurlaili (Jurnal Pengabdian Masyarakat Isei, 2023)
The wife is a friend to the husband in wading through the ups and downs of household life. While the mother is the first teacher in the household madrasah for her children. However, Islam does not prohibit women from working. The wife works, her main motivation is to help her husband meet the economic needs of the family. In working the wife must pay attention to adab which must be maintained according to the view of Islamic law. The problem of family economic needs is the main problem that can often lead to disputes. BPS data shows that the economy is the second most important factor that makes a wife choose to separate. The service was carried out to the people of Dusun V Kampung Baru Kuala Kualu, in this case the women of the Taklim Assembly with a total of 22 respondents who acknowledged that the majority of household problems were due to economic problems. Apart from not having adequate steady income, most of them also do not keep records of family finances. The method is carried out through the provision of education/materials, conducting open discussions, and making an ideal family financial recording simulation.